One dose per day compared to multiple doses per day of gentamicin for treatment of suspected or proven sepsis in neonates - Rao, Shripada C (Cochrane Database Syst Rev, 2016)
BACKGROUND: Animal studies and trials in older children and adults suggest that a 'one dose per day' regimen of gentamicin is superior to a 'multiple doses per day' regimen. OBJECTIVES: To compare the efficacy and safety of one dose per day compared to multiple doses per day of gentamicin in suspected or proven sepsis in neonates. SEARCH METHODS: Eligible studies were identified by searching the Cochrane Central Register of Controlled Trials (CENTRAL; 2016, Issue 3) in the Cochrane Library (searched 8 April 2016), MEDLINE (1966 to 8 April 2016), Embase (1980 to 8 April 2016), and CINAHL (December 1982 to 8 April 2016). SELECTION CRITERIA: All randomised or quasi‐randomised controlled trials comparing one dose per day ('once a day') compared to multiple doses per day ('multiple doses a day') of gentamicin to newborn infants. DATA COLLECTION AND ANALYSIS: Data collection and analysis was performed according to the standards of the Cochrane Neonatal Review Group. MAIN RESULTS: Eleven RCTs were included (N = 574) and 28 excluded. All except one study enrolled infants of more than 32 weeks' gestation. Limited information suggested that infants in both 'once a day' as well as 'multiple doses a day' regimens showed adequate clearance of sepsis (typical RR 1.00, 95% CI 0.84 to 1.19; typical RD 0.00, 95% CI −0.19 to 0.19; 3 trials; N = 37). 'Once a day' gentamicin regimen was associated with fewer failures to attain peak level of at least 5 µg/ml (typical RR 0.22, 95% CI 0.11 to 0.47; typical RD −0.13, 95% CI −0.19 to −0.08; number needed to treat for an additional beneficial outcome (NNTB) = 8; 9 trials; N = 422); and fewer failures to achieve trough levels of 2 µg/ml or less (typical RR 0.38, 95% CI 0.27 to 0.55; typical RD −0.22, 95% CI −0.29 to −0.15; NNTB = 4; 11 trials; N = 503). 'Once a day' gentamicin achieved higher peak levels (MD 2.58, 95% CI 2.26 to 2.89; 10 trials; N = 440) and lower trough levels (MD −0.57, 95% CI −0.69 to −0.44; 10 trials; N = 440) than 'multiple doses a day' regimen. There was no significant difference in ototoxicity between two groups (typical RR 1.69, 95% CI 0.18 to 16.25; typical RD 0.01, 95% CI −0.04 to 0.05; 5 trials; N = 214). Nephrotoxicity was not noted with either of the treatment regimens. Overall, the quality of evidence was considered to be moderate on GRADE analysis, given the small sample size and unclear/high risk of bias in some of the domains in a few of the included studies. AUTHORS' CONCLUSIONS: There is insufficient evidence from the currently available RCTs to conclude whether a 'once a day' or a 'multiple doses a day' regimen of gentamicin is superior in treating proven neonatal sepsis. However, data suggest that pharmacokinetic properties of a 'once a day' gentamicin regimen are superior to a 'multiple doses a day' regimen in that it achieves higher peak levels while avoiding toxic trough levels. There was no change in nephrotoxicity or auditory toxicity. Based on the assessment of pharmacokinetics, a 'once a day regimen' may be superior in treating sepsis in neonates of more than 32 weeks' gestation.